2021
DOI: 10.1111/are.15213
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous probiotics Lactococcus lactis and Weissella confusa in the diet of fingerlings great sturgeon, Huso huso : effects on growth performance, feed efficiency, haematological parameters, immune status and intestinal morphology

Abstract: Sturgeons are one of the most popular and valuable marketable fish species in the world in terms of their caviar and meat. The sturgeon species owing to indiscriminate fishing, water pollution, destroy of spawning places, and construction of dams, are listed as endangered fish by International Union for Conservation of Nature (IUCN, 2018). Today, sturgeon farming has been expanded rapidly in the world. Among the aquaculture of sturgeons, great sturgeon, Huso huso, has made a promising candidate because of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On the other hand, it has been referenced as a bacteriocin-producing bacteria [75], which is a desirable characteristic on account of its ability to prevent the growth of some other pathogens. For its part, W. confusa, which is also an antibacterial compound producer [76], has shown potential to positively impact fish growth performance, as well as stimulate the activity of some digestive enzymes [77]. Similarly, P. russelli has been associated with beneficial effects in terms of fish health and growth, especially regarding activities dealing with protein degradation [78], as elucidated in this paper.…”
Section: Gut Microbiome/fish Performance Correlationsmentioning
confidence: 68%
“…On the other hand, it has been referenced as a bacteriocin-producing bacteria [75], which is a desirable characteristic on account of its ability to prevent the growth of some other pathogens. For its part, W. confusa, which is also an antibacterial compound producer [76], has shown potential to positively impact fish growth performance, as well as stimulate the activity of some digestive enzymes [77]. Similarly, P. russelli has been associated with beneficial effects in terms of fish health and growth, especially regarding activities dealing with protein degradation [78], as elucidated in this paper.…”
Section: Gut Microbiome/fish Performance Correlationsmentioning
confidence: 68%
“…In the present study, therefore, a 56-days' feeding trial was performed for assessing the effects of dietary supplementation with the three autochthonous probiotics on the growth, immune status, and intestinal health of grouper E. coioides fed with high doses of histamine (0.3%). Evidence from several experimental studies shows that dietary supplementation with probiotics can improve growth performance and/or feed utilization in fish such as grouper (E. coioides; Sun et al, 2013;Yang et al, 2019), hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus; ♂ Liao et al, 2021), fingerlings great sturgeon (Huso huso; Rastekenari et al, 2021), rainbow trout (Oncorhynchus mykiss; Mohammadian et al, 2019), and Nile tilapia (Oreochromis niloticus; Doan et al, 2018). In line with this previous research, this study also showed that the administration of the three autochthonous probiotics can improve the growth performance and feed utilization of grouper E. coioides fed with 0.3% histamine, especially in fish fed with diet containing B. pumilus SE5 as probiotic strain (group T2), suggesting that autochthonous probiotics can improve the growth performance and feed utilization of grouper under high histamine stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are many published studies that reported that probiotics can improve the gut morphology and promote gut integrity in several aquatic animals, such as fingerlings great sturgeon ( H. huso ) ( Rastekenari et al, 2021 ), sea cucumber ( Apostichopus japonicus ) ( Zhou et al, 2021 ), Senegalese sole ( Solea senegalensis ) ( Batista et al, 2015 ), and tilapia ( O. niloticus ) ( Standen et al, 2013 , 2016 ). In this study, we found significant improvements in MT and MFH, indicating that the dietary supplementation of autochthonous probiotics ( B. pumilus SE5, Psychrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Aqualase ® (a yeast-based commercial probiotic composed of Saccharomyces cerevisiae and Saccharomyces ellipsoidal) in the feed can moderate the intestinal microbiota of rainbow trout and improve immunity and growth (Adel et al, 2017). The inclusion of 2.5 -2.61*10 7 CFU/kg of two probiotics (Lactococcus lactis and weissella confuse) in the diet can improve the growth performance of fingerling great sturgeon, improve the immune index, and increase the height of intestinal villi (Yeganeh Rastekenari et al, 2021). The fermented dragon fruit in the diet improves the growth performance and feed utilization of Platax pinnatus and increases antioxidant enzyme activity to some extent (Chu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%